PENINGKATAN EFEKTIVITAS PERAWATAN MESIN PERONTOK BULU UNGGAS DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN FAILURE MODE EFFECT ANALYSIS (Studi Kasus di Perusahaan Pengolahan Ayam Kampung Pasuruan) - Rosyidi, Khafizh; Santoso, Purnomo Budi; Sasongko, Mega Nur (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract Perusahaan Pengolahan Ayam Kampung is a company engaged in the processing of chicken that must not be separated from issues related to the effectiveness of the machine. This can be seen with the frequency of damage to the engine due to the damage resulted in a lot of product defects. Therefore we need effective measures in the maintenance of machinery and equipment to tackle and prevent such problems. Total Productive Maintenance (TPM) is a principle of management to improve productivity and efficiency of the production company to use the machine effectively. Not exactly the handling and maintenance of the machine will result in losses that are called by the Big Six Losess. The first step in efforts to increase efficiency in the production of this company is by measuring the effectiveness of the threshing machine feathers using Effectifitas Overall Equipment (OEE) followed by OEE measurement to determine the value of its effectiveness. Next, analysis of causal diagram is to be able to know the real problems that the main cause of losses caused by engine failure. Then, the analysis Failure Mode Effect Analysis (FMEA) was conducted to determine the priority improvements in the next period. The conclusion that can be drawn on the threshing machine feathers that the average value of the OEE for the period September 2013 - August 2014 was 65.14%. This indicates that the ability of thresers feathers in achieving their goals and in achieving effective use of machinery / equipment not yet reached the ideal conditions (â‰¥85%). As for affecting the value of OEE based causal analysis is the lack of maintenance of the machine. Meanwhile, based on the analysis of FMEA can be known priority repairs that need to be done, namely: 1) Perform routine engine maintenance (512), 2) Making standards work (392), and Making Rubber threaded component maintenance schedule (320).